Healing potential of zerumbone ointment on experimental full-thickness excision cutaneous wounds in rat. Issue 3 (August 2017) - Liu, Wayne Young; Tzeng, Thing-Fong; Liu, I-Min
Abstract: Zerumbone is a monocyclic sesquiterpene compound. Based on report, it is the predominant bioactive compound from the rhizomes of Zingiber zerumbet . The study was undertaken to evaluate the therapeutic effects of topical zerumbone on excision wounds in rats. A 1% (w/w) simple ointment containing zerumbone was applied topically (100 mg ointment per rat) once a day on full-thickness excision wounds created on rats. The wound tissue was removed and used for estimation of antioxidant activity and to observe histopathological changes. Immunohistochemical staining was performed to study the expression pattern of vascular endothelial growth factor (VEGF), transforming growth factor (TGF)-β1 and collagen IV. Zerumbone exhibited antimicrobial activity against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Candida albicans and Candida tropicali . Zerumbone ointment has potent wound healing capacity as evident from the wound contraction on 15th post wounding day. The histopathological examinations of healed wound sections showed greater tissue regeneration, more fibroblasts and angiogenesis in zerumbone ointment-treated group. VEGF, TGF-β1 and collagen IV expression were also correlative with the healing pattern observed. Zerumbone possesses potent antioxidant activity by increasing superoxide dismutase, catalase, glutathione and decreased lipid peroxidation. The synergistic effects of both antimicrobial and antioxidant activities in zerumbone are deduced to have accelerated the wound repair. The results demonstrate that zerumbone possessed strong wound healing potential and can be exploited to accelerate excision wound healing. Graphical abstract: Highlights: Zerumbone ointment was applied topically daily to excision wound in rat. Zerumbone treated-healed wound sections showed greater tissue regeneration and more fibroblasts. Expressions of VEGF, TGF-β1 and collagen IV on excision wound were enhanced by zerumbone. We offered a new possible application of zerumbone in the treatment of wound.